Reviews - -- -- (Revista de Lenguas para Fines Específicos, 2015)
• O’Keeffe, Anne, Brian Clancy & Svenja Adolphs. 2011. Introducing pragmatics in use. Abingdon / New York: Routledge. Pp. 188. • Chabner, Davi-Ellen. 2011. The language of medicine in English. St Louis, Missouri: Saunders Elsevier. Pp.1036.